Rwandan policy makers visit Nyando Climate-smart villages - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
From 30 March - 3 April a team from the Ministry of Agriculture and Animal Resources in Rwanda undertook a learning visit of the Nyando CSVs to learn from ongoing initiatives. The officers working under the International Fund for Agricultural Development (IFAD) supported Climate Resilient Post-Harvest and Agribusiness Support Project being implemented in Rwanda. Photos: P.Kimeli (CCAFS).